2021
DOI: 10.1002/asia.202001295
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Terminally Fluorinated [7]Helicenes and Their Application to Photochemical Domino Reactions

Abstract: The intramolecular Diels−Alder reactions of helicenes deform their π‐conjugated screw‐shaped skeletons. In particular, terminally tetrafluorinated [7]helicene (F4‐[7]helicene) undergoes a photoinduced Diels−Alder reaction followed by a photoinduced double fluorine atom transfer. Herein, we thoroughly investigated this photochemical domino process by decreasing the level of fluorine substitution. F3‐[7]Helicenes bearing two fluorine atoms at the dienophile terminal underwent photoinduced Diels−Alder reactions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…On the other hand, changes in ϕ 2 are very small for all the four systems in this case. It is observed that 2F7H shows similar structural features to that of experimentally reported homologous 1,2-difluoro[7]­helicene . Values of R pitch increase by 0.02 Å from 7H to 2F7H .…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…On the other hand, changes in ϕ 2 are very small for all the four systems in this case. It is observed that 2F7H shows similar structural features to that of experimentally reported homologous 1,2-difluoro[7]­helicene . Values of R pitch increase by 0.02 Å from 7H to 2F7H .…”
Section: Resultssupporting
confidence: 81%
“…Keeping this in mind, several modifications have been proposed in recent times ,,, aiming at improving the g -factor and Φ FL . Typical modifications are based on either substitution of hydrogens in helicenes by other atoms/groups or fusion of aromatic rings onto the helical backbone to produce ring-fused carbo­[ n ]­helicenes. Recently, Kubo et al reported dimethoxy and dicyano substituted-carbo[7]­helicenes with improved g CPL values compared to the results for parents systems. While 3.5- and 6-fold increments were obtained for Φ FL and fluorescence rate constant ( K f ), respectively, for dicyanocarbo[5]­helicene, ≥4-fold increments were obtained for the dicyano-carbo[7]­helicene .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The F4 atom obviously accelerates the latter S N Ar process through its strong electron‐withdrawing inductive effect. As a control experiment, we next investigated the reactivity of 2F‐transferred compound 2 b prepared from the photochemical rearrangement of F 3 ‐[7]helicene 1 b (Scheme 2; X=H) [4b] . As with 2 a , the silica gel activated the allylic C−F1 bond of 2 b , but the product in this case was difluorinated ketone 4 b (69 %).…”
Section: Resultsmentioning
confidence: 99%
“…Hypothesizing that this unprecedented elimination of HX should be halogen dependent, we have decided to extend the scope of the reaction towards difluoro and dichloro derivatives 1 b and 1 c, since the Mallory reaction is normally compatible with fluoro and chloro substituents. [1,4,25] Accordingly, starting from the phosphonium salt 3 and using 2,3-difluoro and 2,3dichlorobenzaldehyde we have obtained the two stilbenes 1 b and 1 c as a mixture of Z and E isomers (Scheme 3). Subsequent photocyclization of 1 b and 1 c provided strikingly different results compared to 1 a (Scheme 6).…”
Section: Reactivity Of Dihalostyryl-naphthalenes In Oxidative Photocy...mentioning
confidence: 99%